Implementation of Speech Therapy for Autistic Children at YPAC Medan - Amelia, Anggi; Qarni, Waizul (LP. Ma'arif Janggan Magetan, 2023)
Autism is a disorder of neurobehavioral development with the presence of barriers to brain nerve function related to motor, attention, social and communication functions. Children with autism have problems in the development of communication and interaction, therefore it is necessary to do speech therapy for children with autism. This research was conducted to find out the implementation of speech therapy for autistic children, the obstacles faced by speech therapists in carrying out speech therapy. This research method is a descriptive study using a qualitative approach. Collecting data using interviews, participatory observation, and documentation. The results of this study indicate that the implementation of speech therapy has been going well. This can be seen from the implementation of speech therapy carried out optimally and as a team. Obstacles that occur during the process of implementing speech therapy are the length of time the child's parents provide observations and the obstacles come from children who are hyperactive, therapist time and an environment that is less supportive